2017
DOI: 10.17221/22/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined fertilization with rock phosphate and elemental sulphur on yield and nutrient uptake of soybean

Abstract: Brahim S., Niess A., Pflipsen M., Neuhoff D., Scherer H. (2017): Effect of combined fertilization with rock phosphate and elemental sulphur on yield and nutrient uptake of soybean. Plant Soil Environ., 63: 89-95.Greenhouse pot experiments were carried out in 2013 and 2014 at the University of Bonn, Germany, to study the effect of combined fertilization of rock phosphate (RP) with elemental sulphur (ES) on growth, grain yield and nutrient uptake of soybean. Treatments included RP, ES, combined application (RPES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…These results prove that culture of soybean is highly responsive in negative way to the effect of competition between the species, mainly regarding the light, water and nutrients (Brahim et al, 2017), where metabolism of the plant was impaired and, consequently, the accumulation of DMAPS (Heemst, 1985). Plasticity of adaptation of soybean under competition with others species is varied, as reported by Mckenzie-Gopsill et al (2016), these adaptation or modification reach, in general, the vegetal organism, even at tissues 'level of the organs.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…These results prove that culture of soybean is highly responsive in negative way to the effect of competition between the species, mainly regarding the light, water and nutrients (Brahim et al, 2017), where metabolism of the plant was impaired and, consequently, the accumulation of DMAPS (Heemst, 1985). Plasticity of adaptation of soybean under competition with others species is varied, as reported by Mckenzie-Gopsill et al (2016), these adaptation or modification reach, in general, the vegetal organism, even at tissues 'level of the organs.…”
Section: Resultssupporting
confidence: 52%
“…Spad index of soybean shows a high correlation with nitrogen index in the leaves (Nogueira et al, 2010;Parente et al, 2015), others elements also influence on intensity of green color in leaves, as reported by Brahim (2017) and even the number of leaves in its aerial part, which negatively influenced the rate of photosynthesis as well as dry mass accumulation.…”
Section: Resultsmentioning
confidence: 97%
“…There were no differences in seed yield between ammonium sulphate and urea. In contrast, Brahim et al (2017) reported that the application of magnesium sulphate and/or triple superphosphate significantly increased soybean grain yield, suggesting an effect of sulphate. In our experiment, the higher dose of N (3g N pot -1 ) was a luxury dose, which depressed the yields (treatments 3 and 5) - Table 3.…”
Section: Resultsmentioning
confidence: 89%
“…Elemental sulfur is only taken up by plants after microbial oxidation. However, the effectiveness of elemental sulfur is affected by temperature, moisture, pH, and soil organic matter content due to their influence on the oxidation rate (BRAHIM et al, 2017;DEGRYSE et al, 2018).…”
Section: Forage Productionmentioning
confidence: 99%